Diversidade genética de corynespora cassiicola associada aos hospedeiros soja e algodão - Barreiros, lattes (2025)
Corynespora cassiicola is a phytopathogenic fungus that causes target spot in soybean and cotton, and it also infects other crops of agronomic interest. The objective of this study is to assess the genetic diversity and population structure of C. cassiicola using genomic data. The study was divided into two main parts. In the first part, 55 public genomes of isolates deposited in GenBank were obtained. The isolates were collected in eleven countries and from eight host species. To identify the SNPs between the isolates, Minigraph-Cactus software was used. The phylogenetic analysis revealed a clustering into three main clades, with evidence of host specialization, and with soybean and cotton isolates grouped within the same clade. The second part of the study was focused on the Whole Genome Sequencing of 48 isolates, from which 38 were collected from soybean and 10 were collected from cotton. Isolates with a wide temporal coverage (1997 to 2023) and representing seven Brazilian states were sampled. The SNPs were identified through GATK software. Phylogenetic reconstruction, based on 809,055 SNPs, revealed that the 48 isolates formed two main clades which may represent different phylogenetic lineages. Clade A grouped three soybean isolates considerably distant from the others. Regarding the distribution of the cassiicolin efector gene (Cas), two members of clade A shared an alternative isoform of Cas1. Clade B was divided into two subclades: B1 and B2. Subclade B1 showed a broad and ancient dispersion in the Brazilian territory, grouping 29 soybean isolates collected in seven states between 1997 and 2021. The subclade B1 showed lower genetic diversity and included two Cas isoforms (Cas2 and Cas6). Subclade B2 grouped recent soybean isolates (2021 and 2022) alongside cotton isolates, demonstrating a close relationship between isolates from both crops and suggesting a possible adaptability to both hosts. This evidence is reinforced by the occurrence of an alternative Cas1 isoform in soybean and cotton isolates, exclusive to subclade B2. Different levels of genetic admixture were observed between isolates from the two subclades, indicating the occurrence of recombination through cryptic sexual reproduction or parasexual cycle.